REMOVED: A "cough induced" pelvic fracture as the first sign of a malignant neoplasm. (2015) - Sharma, N.; Sidhu, M.; Simpson, D.
Abstract : This article has been removed: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been removed at the request of the Authors. After publication the authors alerted the journal that the patient had not wanted the report published and that patient consent had not been granted. The article has therefore been removed. Elsevier apologizes for any inconvenience caused.